Family training for the care of people with special needs - bounouiga, nacera (Journal of Social Sciences and Humanities, 2016)
The family is an integral part of therapeutic, counseling, and psychological rehabilitation programs for children with special needs. No intervention plan can achieve its objectives unless it takes into account factors related to the family, its social relationships, and its attitudes toward the child with a disability, as well as the degree of acceptance of having a child with a disability within the family. It is also necessary to consider the impact of the presence of such a child on the lives of other children in the family, as well as its influence on the family’s life cycle and its social relations in general. For this reason, attention to training and professional preparation of the family of the person with a disability is considered a fundamental priority in this field.